2008
DOI: 10.1080/01140670809510221
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature and rainfall on timing of olive (Olea europaea) flowering in southern Italy

Abstract: This study concerns the flowering of the olive (Olea europaea) in a large southern Italian area. It was carried out using the "volumetric" method of pollen sampling and the analysis of the meteorological parameters of temperature and rainfall. The results show that flowering occurs mainly in May, with the maximum values in the second half of the month. Meteorological analysis showed that the biological cycle of the olive was greatly influenced by the temperature. The relationship between an increase of tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 18 publications
2
18
0
2
Order By: Relevance
“…The influence of the meteorological parameters on both pollen emission and pollen dispersion have been widely studied (Recio et al 1996(Recio et al , 1997Galán et al 2001Galán et al , 2005Orlandi et al 2002Orlandi et al , 2010Díaz de la Guardia et al 2003;Vázquez et al 2003;Bonofiglio et al 2008). According to the present study, accumulated variables of temperature and precipitation since the start of the pre-flowering period have been shown to be two of the main factors affecting olive pollen levels.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…The influence of the meteorological parameters on both pollen emission and pollen dispersion have been widely studied (Recio et al 1996(Recio et al , 1997Galán et al 2001Galán et al , 2005Orlandi et al 2002Orlandi et al , 2010Díaz de la Guardia et al 2003;Vázquez et al 2003;Bonofiglio et al 2008). According to the present study, accumulated variables of temperature and precipitation since the start of the pre-flowering period have been shown to be two of the main factors affecting olive pollen levels.…”
Section: Discussionmentioning
confidence: 48%
“…Therefore, wind activity could be other reason to explain the high amounts of pollen registered in Alcalá la Real, which clearly received pollen grains in periods in which there was not effective flowering in the around area. Although meteorological parameters have a clear effect on the olive pollen season, several studies have demonstrated that the olive tree reproductive development is also conditioned by the satisfaction of certain chilling and heat requirements, which differ geographically (Wielgolaski 1999;Orlandi et al 2005;Galán et al 2005;Bonofiglio et al 2008Bonofiglio et al , 2009). Hence, it would be interesting to be able to widen the present study and to relate the altitudinal fluctuations observed in the olive pollen season with different bioclimatic parameters and, therefore, should be considered in subsequent researches.…”
Section: Discussionmentioning
confidence: 99%
“…To examine the relationship between climate and a determined phenological event, the correlation between the values of meteorological parameters registered during the specific period and the starting dates of phenological manifestation were calculated (Jaagus and Ahas 2000;Ahas and Aasa 2006;Emberlin et al 2007;Bonofiglio et al 2008). In our study, to determine the pre-flowering period that greatly influences the olive flowering date, the mean temperature values (calculated in 7 determined pre-flowering periods) were correlated to the flowering dates expressed in days from January 1st (SF and FF).…”
Section: Determination Of the Relationships Between The Flowering Datmentioning
confidence: 99%
“…For the olive, as for many other crops, flowering is a key phenological stage since the sensitivity to extreme events related to heat and water stress during this period significantly affects the final oil yield (Ayerza and Sibbett, 2001;Rapoport et al, 2012). Traditionally, olive flowering date has been estimated by pollen capturing (Galán et al, 2005;Bonofiglio et al, 2008;Avolio et al, 2012;Orlandi et al, 2013) or by simulation models based on phenological observations (Orlandi et al, 2005a). In this sense, different approaches have been considered for flowering date simulation.…”
Section: Introductionmentioning
confidence: 99%